RISK FACTORS OF PREMATURE SEXUAL DEVELOPMENT FORMATION IN GIRLS - Verkhoshanova, O.G. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
On the basis of thorough studying life and disease anamnesis and family anamnesis of 140 girls with premature sexual development (PSD), aged 5 months to 8 years, there have been singled out principal risk factors of PSD formation. Apart from already known factors to them belong  young age of the mother, age difference between the parents more than 8 years, severe gestosis of recent pregnancy, threatened abortion, complicated parturition, delivery by cesarean section, fetus intrauterine hypoxia, postnatal asphyxia, as well as endured diseases and frequent acute respiratory virus infections during the first year of life, and also CNS pathology from birth.